Some plant extracts retarde nitrification in soil - Abdul–Mehdi S. AL-ANSARI; Mohammed A. ABDULKAREEM (Acta Agriculturae Slovenica, 2014)
An incubation experiment was conducted to evaluate the effect of aqueous extracts of 17 plant materials on nitrification inhibition of urea- N in soil as compared with chemical inhibitor Dicyandiamide (DCD). Plant materials used in study were collected from different areas of Basrah province, south of Iraq. Aqueous extracts were prepared at ratio of 1:10 (plant material: water) and added at conc. of 0.05, 0.10 and 0.20 ml g– 1 soil to loamy sand soil. DCD was added to soil at rate of 50 µg g-1 soil . Soil received urea at rate of 1000 µg N g-1 soil. Treated soils were incubated at 30 OC for 40 days. Results showed that application of all plant extracts, except those of casuarina, date palm and eucalyptus to soil retarded nitrification in soil. Caper, Sowthistle ,bladygrass and pomegranate extracts showed highest inhibition percentage (51, 42, 40 and 40 %, respectively) and were found to be more effective than DCD (33 %). Highest inhibition was achieved by using those extracts at conc. of 0.1 ml g-1 soil after 10 days of incubation . Data also revealed that treated soil with these plant extracts significantly increased amount of NH4+–N and decreased amount of NO3-–N accumulation in soil compared with DCD and control treatments. Results of the study suggested a possibility of using aqueous extracts of some studied plants as potent nitrification inhibitor in soil.